Female Identity and Imposed Codes in Caroline Compson: The Influence of Utopia on a Mother - Daniello Edda (Global Writing Academica Researching & Publishing, 2025)
This article will focus on female identity and the codes imposed on the character of Caroline Compson in William Faulkner's novel